Hysteroscopy in Abnormal Uterine Bleeding - Pradhan, Binita; Pun, Isha; Lama, Sushma (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To evaluate the role of hysteroscopy in abnormal uterine bleeding in women of reproductive age group and to correlate the hysteroscopic findings with histopathology. Methods: The study was carried out in the Department of Obstetrics and Gynecology at Patan Academy of Health Sciences, Kathmandu. Thirty patients of age group 20-61years with abnormal uterine bleeding were included. Demonstrable pelvic pathology like cancer of cervix, vagina or endometrium and active pelvic inflammatory disease (PID) were excluded. All patients were assessed using hysteroscopy and findings were correlated with histopathology. Results: On hysteroscopy, endometrium was normal in 30%, hyperplastic in 30%, polyps found in 20% and atrophic in 10%. Endometrial polyp and submucous fibroid was seen in 6.7% cases and 3.3% cases each. On confirmation by histopathology the findings were: normal endometrium in 40% cases, hyperplastic in 40%, polyp in 16.7% and atrophic in 3.3%. Submucous fibroid and suspicious endometrium came to be endometrial hyperplasia on histopathology. Conclusions: Hysteroscopy has more than 90% diagnostic accuracy to diagnose endometrial morphology and diagnostic agreement of endometrial finding is 63.33%. Keywords: abnormal uterine bleeding, hysteroscopy, predictive value